Association of human leukocyte antigen class II with susceptibility to primary biliary cirrhosis: a systematic review and meta-analysis. - Baodong Qin; Jiaqi Wang; Jia Chen; Yan Liang; Zaixing Yang; Renqian Zhong (PLoS ONE)
Purpose Several previous studies suggested that HLA-Class II may be associated with susceptibility to primary biliary cirrhosis (PBC), but data from individual studies remain controversial. Therefore, a systematic review and meta-analysis is needed to comprehensively evaluate the association between HLA-Class II and PBC risk. Methods All published reports of an association between HLA class II and PBC risk were searched in PubMed, EMBASE (updated to 22 May 2012). ORs with 95% confidence intervals (CIs) were extracted from each included study and the meta-analysis was performed using the fixed- or random-effects model. Results A total of 3,732 PBC patients and 11,031 controls from 34 studies were included in the meta-analysis. An assessment of study quality revealed that the majority of studies included (18 studies) were of high quality. The serological group DR8 was found to be a risk factor for PBC (OR = 2.82, 95%CI: 1.84-4.30). At the allelic level, HLA-DR*08 and HLA-DR*0801 were identified as risk factors for PBC (OR = 2.30, 95%CI: 1.76-3.00; OR = 3.23, 95%CI: 2.22-4.70, respectively), whereas HLA-DR*11 and HLA-DR*13 were potent protective factors (OR = 0.31, 95%CI: 0.27-0.38; OR = 0.62, 95%CI: 0.48-0.81, respectively). HLA-DQB1 and HLA-DQB1*0402 conferred a predisposition to PBC development (OR = 3.47, 95%CI: 2.35-5.13), whereas HLA-DQB1*0604 was protective against PBC (OR = 0.3, 95%CI: 0.18-0.58). No HLA-DPB1 allele was observed to be associated with PBC susceptibility (P > 0.05). Conclusions The present study revealed that HLA-Class II components are closely associated with the development of PBC.